2008
DOI: 10.1016/j.canlet.2008.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeted therapy of cancer by omega-3 fatty acids

Abstract: Omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFAs) are essential fatty acids necessary for human health. Currently, the Western diet contains a disproportionally high amount of n-6 PUFAs and low amount of n-3 PUFAs, and the resulting high n-6/n-3 ratio is thought to contribute to cardiovascular disease, inflammation, and cancer. Studies in human populations have linked high consumption of fish or fish oil to reduced risk of colon, prostate and breast cancer, although other studies failed to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
245
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(250 citation statements)
references
References 110 publications
4
245
1
Order By: Relevance
“…Genetic factors are obviously involved in carcinogenesis, but diet is an environmental factor that is likely to have an influence on health (1), and particularly on tumor emergence (2)(3)(4). It has been shown that n-3 polyunsaturated, long-chain fatty acids (PUFAs), such as docosahexaenoic acid (DHA) or eicosapentaenoic acid (EPA), are able to play an important preventive role in cardiovascular disease (5) and cancer (6). This conclusion is based partly on the observation that the incidence of these diseases is lower in Japanese people, whose diet is seafood based, resulting in a more balanced ratio between n-3 and n-6 PUFA than that of the Western diet (7).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors are obviously involved in carcinogenesis, but diet is an environmental factor that is likely to have an influence on health (1), and particularly on tumor emergence (2)(3)(4). It has been shown that n-3 polyunsaturated, long-chain fatty acids (PUFAs), such as docosahexaenoic acid (DHA) or eicosapentaenoic acid (EPA), are able to play an important preventive role in cardiovascular disease (5) and cancer (6). This conclusion is based partly on the observation that the incidence of these diseases is lower in Japanese people, whose diet is seafood based, resulting in a more balanced ratio between n-3 and n-6 PUFA than that of the Western diet (7).…”
Section: Introductionmentioning
confidence: 99%
“…These fatty acids are known to be crucial for normal growth and development (reviewed by Ruxton et al, 2004). They also reduce risk of cardio-vascular disease (reviewed by Givens and Gibbs, 2008), decrease incidence of age-related eye disease (SanGiovanni et al, 2008), positively alter human red blood cell fatty-acid composition (Barcelo-Coblijn et al, 2008), decrease risk of cancer and have a number of other health benefits (Berquin et al, 2008;Li et al, 2008;Mozaffarian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These improvements include an increase in the effectiveness, and a reduction in the toxicity, of drugs prescribed [6,7], thereby producing a better response to CT. At the same time, there has been a considerable decrease in the side effects caused by such treatment, particularly in terms of improvement in appetite and body weight, survival rates and general quality of life, as well as a reduction in the time spent in hospital, and in the gravity of post-surgical infections [6,8,9]. It is extremely important to strengthen the immunological system during oncological treatment [10], since both the CT and the cancer itself can have a direct effect on it [1].…”
Section: Role Of Nutrition In Cancer Chemotherapymentioning
confidence: 99%